Assessment of microbiological quality of municipal supplied water within Dhaka Metropolis (Stamford Journal of Microbiology, 2015)
Microbiological health risks related to water quality are persisting issues especially in the developing countries. Present study was conducted to evaluate the microbiological quality of municipal supply water of a defined region within Dhaka metropolis, Bangladesh. A total of 20 water samples were collected from 10 selected pump stations and 10 different consuming points to examine the burden of Salmonella spp., Shigella spp., Citrobactor spp., Escherichia coli, Klebsiella spp., Aeromonas spp. and Vibrio spp. The study also included the evaluation of impacts due to the consumption of municipal water. The results revealed that the quality of municipal supplied water was not microbiologically safe for the consumers and also demonstrated the possible commencement of various diseases including diarrhoea, typhoid, dysentery and others. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22758 Stamford Journal of Microbiology, Vol.4(1) 2014: 28-30